Guidelines for Failure Investigation. - Investigations, Committee on Forensic; Barrow, Richard; W. Anthony, Ronald; J. Beasley, Kimball; M. Verhulst, Stewart (Reston : American Society of Civil Engineers, 2018)
This book outlines the fundamental steps that will assist forensic engineers in tailoring their forensic investigations of failures and performance problems associated with structures and building systems.
6.4.11 Avoid or Define Ambiguous Words -- 6.4.12 Use Quotes Rather Than Paraphrasing -- 6.4.13 Use Engineering Judgment Appropriately -- 6.4.14 Use Appropriate Graphics -- 6.4.15 Cite and Append Supporting Materials -- Appendix A: Code of Ethics1 -- Appendix B: Glossary of Terms -- Appendix C: Additional Recommended Reading -- Index -- Chapter 1: Functions and Responsibilities of the Forensic Engineer -- 1.1 INTRODUCTION TO FORENSIC ENGINEERING -- 1.2 NEED FOR FAILURE INVESTIGATIONS -- 1.3 THE FORENSIC ENGINEERING INVESTIGATIVE PROCESS -- 1.4 THE PRINCIPAL INVESTIGATOR -- 1.4.1 Knowledge of the Field of Expertise -- 1.4.2 Qualities of Character -- 1.5 THE LEGAL ENVIRONMENT -- 1.6 CONCLUSION -- References.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Structural failures-Investigation.; Electronic books